Robot autonomous judgment system based on improved computer algorithm - Liu, Xianhua (International journal of system assurance engineering and management, 2023)
According to the characteristics of the physical model of autonomous robot, such as strong nonlinearity and many external interference factors, a robot autonomous judgment system based on computer algorithm is proposed in this paper. The system can accomplish the approximate linearization of decomposed variables by using dynamic feedback control algorithm, so as to achieve the purpose of initial effective control. The adaptive performance of computer algorithm can effectively solve the compensation control needed by uncertain model and other disturbances. Finally, the proposed algorithm is verified by using MATLAB simulation software. The experimental results show that the proposed algorithm has good dynamic performance and strong robustness.